U.S. Economic Diplomacy towards Japan in Resolving Beef Tariff Barriers - Andrea Gladys Gabriella; Shanti Darmastuti; Wiwiek Rukmi Dwi Astuti (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2023)
The United States (US) is one of beef exporting countries in Japan. The high level of demand for beef in Japan was followed by a decrease in the volume of US beef from Japan during 2017-2020 period caused by import barriers in the form of tariffs faced by US beef. These tariff barriers arise because the US does not have a trade agreement with Japan. This study aims to discuss the efforts made by the US through negotiating tariff barriers with Japan regarding beef exports. This study uses the concepts of economic diplomacy and trade theory as the basis for research analysis. The research method used in this research is descriptive qualitative with data collection through documentation study. The results of this study indicate that the US effort in negotiating tariff barriers with Japan is to form a bilateral trade agreement, namely the US-Japan Trade Agreement (USJTA) which uses the stages of decision-making in economic diplomacy in its formation. Through this effort, the US successfully lowered its beef import tariffs in Japan and leveled its beef competitive level with the CPTPP member countries. In the formation of the USJTA, various actors are involved, both state and non-state actors. Efforts to negotiate tariff barriers on beef exports by the US and Japan succeeded in increasing US beef exports after the establishment of the USJTA began to be implemented on January 1, 2020. Keywords: economic diplomacy, export, tariff barriers, United States